An external auditory canal swelling: a pseudo meningocele - Bidkar, Vijay G.; Chavan, Vaibhav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The author presents a case of an external auditory canal swelling. A pseudo meningocele, delayed complication of mastoidectomy. Differential diagnosis of swelling in the ear canal includes various conditions. The study aims to discuss management and review the literature of this uncommon condition. A 34-year lady presented with right ear canal swelling, reduced hearing and occasional watery ear discharge. Patient had undergone ear surgery 14 years back. Radiological studies including computed tomography and magnetic resonance imaging were suggestive of defect in the tegmen and posterior canal wall and presence of swelling containing cerebrospinal fluid (CSF) in mastoid cavity. Post aural trans mastoid approach was planned and multi layered closure of the defect was done under adequate antibiotic coverage. Pseudo meningocele may manifest as delayed complication of mastoid surgery and risk of meningitis is higher as CSF containment to its space is failed. Trans mastoid resection of swelling and reconstruction of the skull base is preferred modality of treatment considering size of the defect.